2015
DOI: 10.1128/jcm.01922-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BD Max StaphSR Assay for Rapid Identification of Staphylococcus aureus and Methicillin-Resistant S. aureus in Positive Blood Culture Broths

Abstract: bWe evaluated the performance of the BD Max StaphSR assay for the direct detection of Staphylococcus aureus from blood culture medium. In a two-center trial, 155 blood cultures from the BD Bactec FX system and 212 from the bioMérieux BacT/Alert system were tested; 170 bottles yielded S. aureus, and all were identified correctly by the BD Max StaphSR assay. The assay required approximately 2.5 h, thus allowing rapid identification of blood cultures flagged positive. The BD Max StaphSR assay (BD, Quebec, Canada)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…In this study, we obtained Ct values from BD and found that the Ct value distribution for the nuc gene was clearly separate, and the highest Ct value among the S. aureus was 25.6 including mixed infections. This is in line with another study where the Ct values for the nuc target were <27 for all MRSA-positive blood cultures [8]; therefore, we selected a Ct value <27 to indicate positivity.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, we obtained Ct values from BD and found that the Ct value distribution for the nuc gene was clearly separate, and the highest Ct value among the S. aureus was 25.6 including mixed infections. This is in line with another study where the Ct values for the nuc target were <27 for all MRSA-positive blood cultures [8]; therefore, we selected a Ct value <27 to indicate positivity.…”
Section: Discussionsupporting
confidence: 69%
“…The BD Max TM StaphSR Assay (BD Diagnostic Systems, Qu ebec, Canada) is a CE marked and FDA approved, fully automated diagnostic test which was developed for detection of S. aureus and MRSA in patients at risk for nasal colonization [34]. The test is based on a multiplex real-time PCR and differentiates S. aureus and MRSA by detecting the presence of the nuc and mecA/C genes, and the SCCmec-orfX junction within approximately 2.5 hours [34]. Although the BD Max TM StaphSR Assay was designed for rapid screening of nasal swabs, the performance of the test was also analysed for detecting S. aureus and MRSA from positive BCs [34e36].…”
Section: Bd Max Tm Staphsr Assaymentioning
confidence: 99%
“…However, six out of eight isolates in fact carried the mecA gene, which would provide a corrected specificity rate of 99.8%. Other studies performed in the United States and Europe have reported sensitivity and specificity rates of Ն94.3% and Ն97.7%, respectively (29,30). However, it is important to mention that these studies evaluated the performance of the BD Max StaphSR from nasal swab samples or directly from blood specimens.…”
mentioning
confidence: 98%